Low temperature X-ray absorption spectroscopy study of CuMoO4 and CuMo0.90W0.10O4 using reverse Monte-Carlo method - Jonane, Inga; Cintins, Arturs; Kalinko, Aleksandr; Chernikov, Roman; Kuzmin, Alexei (Elsevier Ltd, 2019)
Reversible thermochromic phase transition between α- and γ-phases was studied in CuMoO4 and CuMo0.90W0.10O4 using X-ray absorption spectroscopy in the temperature range of 10–300 K. Reverse Monte Carlo modelling with evolutionary algorithm approach at several absorption edges simultaneously was applied to extract structural information encoded in the experimental EXAFS spectra. The obtained results show that an addition of 10 mol% of tungsten to CuMoO4 induces local distortions in the structure and stabilizes the γ-phase, leading to an increase of the phase transition temperature by ~50–100 K.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; CuMoO4; EXAFS; Reverse Monte Carlo; X-ray absorption spectroscopy; XANES